(y+5/3)-3=6

Simple and best practice solution for (y+5/3)-3=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y+5/3)-3=6 equation:


(y+5/3)-3=6

We simplify the equation to the form, which is simple to understand
(y+5/3)-3=6

Simplifying:
(y+1.66666666667)-3=6

Remove unnecessary parentheses
y+1.66666666667-3=6

We move all terms containing y to the left and all other terms to the right.
+1y=+6-1.66666666667+3

We simplify left and right side of the equation.
+1y=+7.33333333333

We divide both sides of the equation by 1 to get y.
y=7.33333333333

See similar equations:

| 5e-6-4=-3 | | x(2x-2)+x(3x-4)=(5x+6)(x-4) | | -126=14*k | | 6z+5(z-6)= | | (5e-6)-4=-3 | | 4x-1-4x+7= | | 4x+x=-27 | | 21=-7*n | | -13=-8b-5b | | -6x-50+12x=64 | | 4x-4=27 | | 0.15x+0.6(x-2)=0.01(3x-5) | | 5(-5)-2(2)= | | 11t/28-t/4=1 | | x-2(3x-2)=-6+4x-8 | | -15*x=2 | | g(-x)=x^2+10x+35 | | 5-4(3m-6)=5 | | 4(3+1.25)+5y=12.00 | | 6y+3-8=-37 | | 5x+6x-(3x+5)= | | V+9=1 | | x^3-6x+9x=0 | | 6n+4+2=-24 | | -10-5(1+j)= | | -2x+1=-2(x+5) | | 6x-8+8=6 | | 3(-9h+10)= | | 13/1/3 | | 3(x^2-1)=24 | | 5(-7g-2)= | | 5/2(n-92) |

Equations solver categories